Proportional-Integral-Derivative and Linear Quadratic Regulator Control of Direct Current Motor Position using Multi-Turn Based on LabView - Devi Handaya; Resti Fauziah (Universitas Muhammadiyah Yogyakarta, 2021)
This study accommodates the industry needs in monitoring a control system on a DC motor using LabView. The servomotor, which is usually used for position control, was replaced in this study with a DC motor coupled with a multi-turn potentiometer sensor. The use of DC motors was carried out to reduce actuator prices while maintaining control objectives. The control method used is in the form of Proportional – Integral - Derivative (PID) and optimal control which are then compared with the output. PID tuning is done using the Root Locus method. Meanwhile, for optimal control using the Linear Quadratic Regulation (LQR) approach. Testing was done by looking at the results of direct implementation of the DC motor plant hardware through observations using LabView. By using the right zero variables in the PID control, the best performance is obtained until it can track references. Too large a zero value will result in even greater Steady State Error. The results of optimal control using different Q variables did not provide a significant change. The SSE value shows the same result. The results show that the optimal control can track the reference with lower settling time and overshoot than the PID control. However, the two control methods still produce relatively small Steady State Error.